2010
DOI: 10.1007/s11055-010-9342-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Visual Environment Complexity on Saccade Performance in Humans with Different Functional Asymmetry Profiles

Abstract: Studies in 47 right-handed subjects with right and left leading eyes addressed the latent periods of visually-evoked saccades in the horizontal, vertical, and diagonal directions within the field of vision. Visual environments with three levels of temporospatial complexity and two standard time protocols of visual stimulation, with "gap" and "overlap," were used. In subjects with left leading eyes, saccades were more often performed with shorter latent periods in the direction ipsilateral to the leading eye th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Very few studies have evaluated the effect of eye dominance but again without consistent results. 2,21,22 The present study tested these asymmetries on a large sample of participants, and failed to find any left-right asymmetries on saccade latency. The fact that RDE did not differ between the two hemifields in participants with strong eye dominance suggests that eye dominance does not influence saccade latency, at least in the conditions we tested.…”
Section: Remote Distractor Effectmentioning
confidence: 55%
See 1 more Smart Citation
“…Very few studies have evaluated the effect of eye dominance but again without consistent results. 2,21,22 The present study tested these asymmetries on a large sample of participants, and failed to find any left-right asymmetries on saccade latency. The fact that RDE did not differ between the two hemifields in participants with strong eye dominance suggests that eye dominance does not influence saccade latency, at least in the conditions we tested.…”
Section: Remote Distractor Effectmentioning
confidence: 55%
“…Participants with a strong right DE seemed to show the reverse effect, with a distractor impact greater in the right than in the left hemifield, but the difference failed to reach the significance threshold ( Fig. 3a; F [1,21] ¼ 2.92, P < 0.10). However, it should be noted that an effect of eye dominance strength was found in the right hemifield in participants with a right DE (F [1,55] Participants were categorized into four groups according to their eye dominance (right DE; left DE) and eye dominance strength (strong; weak).…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, taking into account the advantage in faster elicitation times, the goal of our research is to design a stimulus that supports the use of reflexive saccades for biometric authentication. For example, prior research has shown that saccade latencies depend on the dominant eye [32] of the individual, which is a stable characteristic and provides strong motivation for using saccade latencies for classification. Finally, it was shown that saccade latency varies if anticipation (temporal expectancy) is present [46].…”
Section: Analysis Of Reflexive Eye Movements For Fast Replay-mentioning
confidence: 99%
“…Furthermore, taking into account the advantage in faster elicitation times, the goal of our research is to design a stimulus that supports the use of reflexive saccades for biometric authentication. For example, prior research has shown that saccade latencies depend on the dominant eye [31,26] of the individual, which is a stable characteristic and provides strong motivation for using saccade latencies for classification. Finally, it was shown that saccade latency varies if anticipation (temporal expectancy) is present [40].…”
Section: Background On Eye Movementsmentioning
confidence: 99%